THU0565 Needs assessment of training in paediatric rheumatology among spanish paediatricians. multicenter descriptive study. (12th June 2018) - Udaondo, C.; Murias, S.; Alcobendas, R.; Remesal, A.
Abstract : Background: There is a perception that care for paediatric patients with pathology Rheumatic is heterogeneous, as several previous publications have shown. Likewise, in Spain we do not have the recognition of a specialisation in Rheumatology Paediatric, for which it is possible that the training in this field is not sufficiently specific. This could be detrimental to the best care received on the part of the patients. Paediatric rheumatology has some specific characteristics that make it unique, but there is yet no recognised specialisation in some countries. Objectives: To examine the needs assessment for specific training in paediatric rheumatology among paediatricians and paediatricians in training from different countries using a specific questionnaire. Methods: An online anonymous questionnaire was sent to paediatricians and paediatricians in training from different centres in Spain, London an Mexico. Data on working place, city, and perception of the state of training in paediatric rheumathology in their workplace were collected. Results: A total of 447 questionnaires were answered: 287 by senior paediatricians (64.5%) and 125 by paediatric trainees (28.1%); 96.4% in different Spanish cities and 3.6% 16 a in other countries. For 54.7% (254) of the respondents there is no specialisation in paediatric rheumatology in their workplace. The main responsible of children with rheumatic pathology is a paediatric rheumathologist in 59.7% (257) cases, with or without recognised specialisation, a general paediatrician in 21.2% (91) cases and an adult rheumathologist in 19.1% (82) cases. 96.8% of the respondents believe that there should be an accredited training in paediatric rheumatology. The formative aspects that were believed to be more important were the knowledge in paediatric rheumatology, general paediatrics and immunology, and the most valued capacities were the physical exploration, arthrocentesis and infiltration and the performance of musculoskeletal ultrasound. Conclusions: The majority of paediatricians reached believe there is a lack of recognised specialisation in paediatric rheumatohology in Spain, and a need for accredited training. The attention to children with rheumathic diseases in Spain is heterogeneous. This survey reinforces the perception that training in paediatric rheumatology in our country should be improved. References: [1] De Inocencio J, Antón J.Reumatologia pediátrica. Breve historia y situación de la especialidad en España. Acta Rheumatologica2014;1:1. [2] Spencer CH. Why should pediatric rheumatology be recognized as a separate subspecialty: An open letter to medical councils and government agencies. Pediatr Rheumatol Online J2007;21:21. [3] Passo M. Status Report for Pediatric Rheumatology: What Needs to Be Done?Arthritis & Rheumatism (Arthritis Care & Research)2006December 15;55(6):833–835. [4] Woodward AL, Harris ZL. Employment of a needs assessment survey to shape a novel web-based pediatric rheumatology curriculum for primary care providers. Pediatric Rheumatology2013;11:26. Acknowledgements: Dr. Lacassagne, Dr Khaosut and Dr Sifuentes. Great Ormond Street Hospital, London. Disclosure of Interest: None declared